2003
DOI: 10.1046/j.1442-2042.2003.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic carcinosarcoma: A case report and review of literature

Abstract: A unique case of carcinosarcoma of the prostate detected in a 71-year-old man is presented. Pelvic exenteration was performed, and the resected prostatic mass was found to consist of two histologically distinct elements; adenocarcinoma and sarcoma with focal osteosarcomatous element. The patient is still alive with neither metastasis nor recurrence. This is the 42nd case of carcinosarcoma of the prostate to be reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…Interestingly, some cases were reported to be adenosquamous carcinoma, which may be associated with chondrosarcoma development [6,17]. The most common sarcomatous component was reported to be osteosarcoma (50-62%) followed by chondrosarcoma (33-45%), leiomyosarcoma (17-24%), and rhabdomyosarcoma (10-12%) [6,7]. In the present case, the sarcomatous component was leimomyosarcoma based on the immunohistochemical findings showing positive reaction with α-SMA.…”
Section: Case Presentationmentioning
confidence: 62%
See 3 more Smart Citations
“…Interestingly, some cases were reported to be adenosquamous carcinoma, which may be associated with chondrosarcoma development [6,17]. The most common sarcomatous component was reported to be osteosarcoma (50-62%) followed by chondrosarcoma (33-45%), leiomyosarcoma (17-24%), and rhabdomyosarcoma (10-12%) [6,7]. In the present case, the sarcomatous component was leimomyosarcoma based on the immunohistochemical findings showing positive reaction with α-SMA.…”
Section: Case Presentationmentioning
confidence: 62%
“…The origin and pathogenesis of PCSs is still unknown; some authors proposed that both carcinoma and sarcoma simultaneously developed within the prostate, while others suggested that adenocarcinoma underwent transformation into sarcoma [7,9,14,15]. The present case was suggested to be the latter case from the findings of histopathological re-examination of the biopsy.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Radiotherapy, surgery, hormonal therapy or chemotherapy were used in the treatment but the results of treatment were not satisfactory. The survival was found to be 7 months and there were no predictive parameters to detect it (14). In our case, carcinosarcoma was common in the tissue; and even no metastases was seen, the survival was about 5 months.…”
Section: Discussionmentioning
confidence: 85%